2008
DOI: 10.1097/brs.0b013e31816956de
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Atlas Fractures

Abstract: The presented results strongly suggest that the Type of atlas fracture depends on the speed of axial force impact. The present study demonstrates that Type-III fractures (2- to 4-part burst fractures) result from fast force impact whereas slow force impact is responsible for Type-IV atlas fractures of the lateral mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The maximum stress value of the atlas plate was 0.176 × 10 9 N / m 2 and the stress was mainly focused on screw holes and the contact with the artificial dens (above the left lateral wall of dens hole). The maximum stress value at axis plate was 0.345 × 10 9 N / m 2 which was concentrated on the anterior arch and posterior arch (9). Our study demonstrated that after the AAOJ replacement, stress increased on the screw holes and the junction of lateral mass -posterior arch, the stress at a hole was gradually transferred to its periphery, while the stress at the junction of lateral mass -posterior arch passed to posterior arch.…”
Section: Fe Analysis On the Biomechanical Properties Of Aaoj Componenmentioning
confidence: 55%
“…The maximum stress value of the atlas plate was 0.176 × 10 9 N / m 2 and the stress was mainly focused on screw holes and the contact with the artificial dens (above the left lateral wall of dens hole). The maximum stress value at axis plate was 0.345 × 10 9 N / m 2 which was concentrated on the anterior arch and posterior arch (9). Our study demonstrated that after the AAOJ replacement, stress increased on the screw holes and the junction of lateral mass -posterior arch, the stress at a hole was gradually transferred to its periphery, while the stress at the junction of lateral mass -posterior arch passed to posterior arch.…”
Section: Fe Analysis On the Biomechanical Properties Of Aaoj Componenmentioning
confidence: 55%
“…The normal range of axial rotation of the atlas on the axis is from 43 to 56° [ 10 ]. Based on an average atlas transverse diameter of 79.6 mm [ 11 ], lateral rotation to a displacement of 10 mm, corresponding to 15° of rotation, is well within the normal limits of rotation. This was deemed important as the purpose of this study was to assess the relative contributions of the bony and soft tissue structures within the C1-C2 complex and thus we wanted the mechanical analysis to evaluate the effect of our dissections, rather than disrupt the complex in any way.…”
Section: Methodsmentioning
confidence: 99%
“…1 ) due to the sloping surface of the atlantoaxial articulation. 1 9 Isolated posterior arch fractures of the atlas may result from the pinching of the posterior arch between a hyperextended occiput and C2 spinous process. 1 10 High-speed impact leads to classic burst fracture and slow speed trauma leads to LM fractures.…”
Section: Injury Mechanism and Pathological Anatomymentioning
confidence: 99%
“…These fractures correlate directly to osteoporosis. 9 The atlantoaxial joint contributes nearly 50% to the observed range of neck rotation. 11 Due to the contrasting demands posed by requirements of rotational freedom and resilience of craniocervical articulation, ligaments have a disproportionate role in stabilizing this region of the cervical spine as compared with the shape of articular surfaces.…”
Section: Injury Mechanism and Pathological Anatomymentioning
confidence: 99%